Hydraulic controls of in‐stream gravel bar hyporheic exchange and reactions. Issue 4 (11th April 2015) - Trauth, Nico; Schmidt, Christian; Vieweg, Michael; Oswald, Sascha E.; Fleckenstein, Jan H.
Abstract Hyporheic exchange transports solutes into the subsurface where they can undergo biogeochemical transformations, affecting fluvial water quality and ecology. A three‐dimensional numerical model of a natural in‐stream gravel bar (20 m × 6 m) is presented. Multiple steady state streamflow is simulated with a computational fluid dynamics code that is sequentially coupled to a reactive transport groundwater model via the hydraulic head distribution at the streambed. Ambient groundwater flow is considered by scenarios of neutral, gaining, and losing conditions. The transformation of oxygen, nitrate, and dissolved organic carbon by aerobic respiration and denitrification in the hyporheic zone are modeled, as is the denitrification of groundwater‐borne nitrate when mixed with stream‐sourced carbon. In contrast to fully submerged structures, hyporheic exchange flux decreases with increasing stream discharge, due to decreasing hydraulic head gradients across the partially submerged structure. Hyporheic residence time distributions are skewed in the log‐space with medians of up to 8 h and shift to symmetric distributions with increasing level of submergence. Solute turnover is mainly controlled by residence times and the extent of the hyporheic exchange flow, which defines the potential reaction area. Although streamflow is the primary driver of hyporheic exchange, its impact on hyporheic exchange flux, residence times, and solute turnover is small, as these quantities exponentially decrease under losing and gaining conditions. Hence, highest reaction potential exists under neutral conditions, when the capacity for denitrification in the partially submerged structure can be orders of magnitude higher than in fully submerged structures.